Making the Familiar Strange: An Ethnographic Scholarship of Integration Contextualizing Engineering Educational Culture as Masculine and Competitive. Issue 3 (2nd September 2019) - Secules, Stephen
Abstract : This paper emerges out of ethnographic scholarship on marginalization in present-day engineering education. I pursue a scholarship of integration to contextualize my own and others' engineering education research with critical, cultural, and historical accounts of engineering. I structure the narrative around the ethnographic themes of masculinity, competition, and competition-as-masculinity. Within each theme I situate present-day ethnographic observations of engineering educational culture, elaborate on those observations with historical context, and return to consider how historical context extends the original ethnographic observations. The implications for the study are threefold: (1) generating a new functional lens on engineering educational culture as masculine and competitive, (2) communicating useful historical context to stakeholders in engineering education, and (3) demonstrating the value of integrative scholarship to promote further interdisciplinary collaboration.